The Impact of Hyperbole on the Perception of Testimonies from Victims of Sexual Crime - Desai, Shreyasi (2023)
Hyperbole is a figure of speech which enhances emotionality by emphasising speaker intentions and evaluations. While hyperbole itself has not been studied in victim speech, emotionality is believed to be a deciding factor in forensic decisions. This thesis focuses on the language of victim testimony and related factors that make a ‘credible rape victim’ for forensically relevant groups. The topic is explored using a reverse funnel approach and mixed methods investigating the impact of hyperbole on victim testimony (Experiments 1 and 2), the preference of hyperbolic or literal language in victim testimony (Experiment 3), the role of hyperbole in establishing emotionality (Experiment 4), and finally, a qualitative analysis of impactful factors in victim perception other than hyperbole (Studies 5 and 6). Results indicate that (1) hyperbole performs different affective functions depending on the participant group: decreasing credibility for law enforcement while increasing credibility ratings for laypersons; (2) hyperbole increases emotional intensity for observers, but group differences in hyperbolic preferences persist such that laypersons prefer to use hyperbole and law enforcement participants remain disinclined; (3) when exploring professional perceptions of victims, it may be hyperbolic agency which ultimately negates hyperbolic emotionality and harms credibility and linguistic preference ratings. Figurative language in forensic settings is relatively unexplored, and hence suggestions are made for further studies on hyperbole in isolation as well as its role as an agent of conveyed emotionality.